2022
DOI: 10.3390/cells11060946
|View full text |Cite
|
Sign up to set email alerts
|

Batch Effects during Human Bone Marrow Stromal Cell Propagation Prevail Donor Variation and Culture Duration: Impact on Genotype, Phenotype and Function

Abstract: Donor variation is a prominent critical issue limiting the applicability of cell-based therapies. We hypothesized that batch effects during propagation of bone marrow stromal cells (BMSCs) in human platelet lysate (hPL), replacing fetal bovine serum (FBS), can affect phenotypic and functional variability. We therefore investigated the impact of donor variation, hPL- vs. FBS-driven propagation and exhaustive proliferation, on BMSC epigenome, transcriptome, phenotype, coagulation risk and osteochondral regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…To minimize the influence of in vitro culture conditions, similar isolation methods and identical culture conditions were chosen for all cell types as established and validated previously (20). There is substantial evidence that hPL supports culture expansion of various stromal cell types better than FBS or human serum without compromising their regenerative capacity (49)(50)(51).…”
Section: Origin Culture Identity and Purity Of Stromal Cellsmentioning
confidence: 99%
“…To minimize the influence of in vitro culture conditions, similar isolation methods and identical culture conditions were chosen for all cell types as established and validated previously (20). There is substantial evidence that hPL supports culture expansion of various stromal cell types better than FBS or human serum without compromising their regenerative capacity (49)(50)(51).…”
Section: Origin Culture Identity and Purity Of Stromal Cellsmentioning
confidence: 99%
“…Exposure of cells to FBS during isolation and expansion steps might affect the cell phenotype and their differentiation capacity. A recent study showed that BMSCs lost their chondrogenic potential after expansion in FBS containing medium [82]. Thus, the serum substitute medium for hBMSCs isolation and expansion also needs to be optimized to have fully FBS-free studies.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards the sections were washed in acetic acid n -butyl ester (P036.1 Roth) and mounted. Cartilage (proteoglycan specific) stains bright red and the backgrounds stains in green [ 47 ]. For Masson–Goldner trichrome and elastica staining, kits were used according to the manufacturer’s recommendations (Morphisto 12043, Morphisto 14604) [ 48 ].…”
Section: Methodsmentioning
confidence: 99%